(untitled) (Journal of Enam Medical College, 2014)
Correction: On the website, on 16/08/2014, the first author was changed from Md Aminul Khan TO Md Aminul Haque Khan. The PDF was correct. The most widely used investigation of renal function and GFR is the measurement of serum creatinine and creatinine clearance rate. This has been extremely popular in clinical medicine despite formidable difficulties associated with its quantification and interpretation. The main pathophysiological difficulties include variations in the rates of creatinine generation and its secretion by the renal tubules. Concentration of serum creatinine is now recognized as an unreliable measure of kidney function as it is affected by age, body weight, muscle mass, race and various medications. Several equations have been developed to improve the accuracy of serum creatinine level as a measure of GFR. The most widely used in adult populations are the Cockroft-Gault equation and the abbreviated Modification of Diet in Renal Disease (MDRD) equation. Even with these equations, measurement of GFR is difficult because the equations are less accurate with higher levels of kidney function and are affected by interlaboratory variation in measuring creatinine level. In the above perspective, cystatin C concentration has become a promising marker for kidney function in both native and transplanted kidneys. Because of the possible potentiality of cystatin C to be an emerging endogenous marker for quick and accurate assessment of renal function, we have decided to review elaborately on cystatin C as a marker of renal function and to review the sensitivity and specificity of cystatin C as an endogenous marker compared to serum creatinine. Results of our review study suggest that cystatin C is a better marker of renal function compared to serum creatinine and other endogenous markers irrespective of age, sex and clinical condition. DOI: http://dx.doi.org/10.3329/jemc.v4i2.19680 J Enam Med Col 2014; 4(2): 110-122